2015
DOI: 10.1016/j.neuron.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Acute Stress Impairs Self-Control in Goal-Directed Choice by Altering Multiple Functional Connections within the Brain’s Decision Circuits

Abstract: Important decisions are often made under stressful circumstances that might compromise self-regulatory behavior. Yet the neural mechanisms by which stress influences self-control choices are unclear. We investigated these mechanisms in human participants who faced self-control dilemmas over food reward while undergoing fMRI following stress. We found that stress increased the influence of immediately rewarding taste attributes on choice and reduced self-control. This choice pattern was accompanied by increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
196
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(222 citation statements)
references
References 63 publications
21
196
4
1
Order By: Relevance
“…Indeed, regulation training has been shown to produce robust fear reduction in non-stressed participants but not stressed participants (Raio et al., 2013). A recent neuroimaging study also found that acute stress impairs self-control in goal-directed choice by reducing connectivity between ventromedial PFC and dorsolateral PFC regions linked to self-control success (Maier et al., 2015). These results highlight critical limitations of this technique to control affective responses under stress; other techniques such as emotion regulation strategies may also have limited power to overcome stress-biased decisions.…”
Section: Stressors Potentiate Decision Biasesmentioning
confidence: 98%
“…Indeed, regulation training has been shown to produce robust fear reduction in non-stressed participants but not stressed participants (Raio et al., 2013). A recent neuroimaging study also found that acute stress impairs self-control in goal-directed choice by reducing connectivity between ventromedial PFC and dorsolateral PFC regions linked to self-control success (Maier et al., 2015). These results highlight critical limitations of this technique to control affective responses under stress; other techniques such as emotion regulation strategies may also have limited power to overcome stress-biased decisions.…”
Section: Stressors Potentiate Decision Biasesmentioning
confidence: 98%
“…The benefits of moving in a translational direction to inform clinical work and ameliorate everyday lives cannot be overstated. For instance, individuals may have difficulties using emotion regulation strategies under stress [88] which could lead to deficits in decision making such as reduced self-control [89]. Increasing positive emotion [90] or fostering a perception of control in the face of stress could serve as alternative coping mechanisms with potential consequences for decision making, such as promoting persistence in goal pursuit [91].…”
Section: Future Directionsmentioning
confidence: 99%
“…These women also demonstrated greater consumption of high-calorie foods after the scanning session. In a similar vein, Maier et al (215) compared the neural responses between participants assigned to a laboratory stressor versus those assigned to a neutral condition during a food choice task. Subjects assigned to the stressor put greater value on the taste of the food items presented.…”
Section: Clinical Evidencementioning
confidence: 99%
“…Paralleling this, bilateral amygdala and right nucleus accumbens reflected the relative taste value of chosen options more strongly in stressed compared to control participants. The authors interpreted these findings as suggesting that acute stress may increase the rewarding attributes of food stimuli (215). Furthermore, Jastreboff et al (216) observed that obese individuals exhibit increased activation in striatal, insular, and hypothalamic regions in response to stress and favorite-palatable food cues compared to lean individuals.…”
Section: Clinical Evidencementioning
confidence: 99%